Current account deficits in the new member states: Causes and consequences - Robert C. Schelburne (Intereconomics, 2009)
Rapidly growing and fundamentally sound economies like those of the new EU member states should be able to borrow externally and thereby run large current account deficits for a considerable period of time. They have been doing this for almost a decade and as a result their businesses have been able to invest more and their residents consume more than would have been possible otherwise. That development model is now being tested severely by the current fi nancial crisis. The degree to which they will be able to maintain capital infl ows and growth over the next year will have important implications not only for them, but for what is generally considered to be a desirable development model. The world's overall assessment of the acceptability of, and the need for, a fundamental reform of the current international monetary architecture will also depend critically on what happens in these economies.
Keywords: 330